2006
DOI: 10.1590/s1413-70542006000600010
|View full text |Cite
|
Sign up to set email alerts
|

Teores de macronutrientes em mudas de aceroleira (Malpighia emarginata DC.) em função da composição do substrato

Abstract: RESUMOA composição do substrato com diferentes fontes de matéria orgânica é considerado como um elemento chave na obtenção de mudas de boa qualidade. Assim, com este estudo objetivou-se avaliar a melhor fonte e a melhor quantidade de matéria orgânica que poderá ser usada para a produção de mudas de aceroleira (Malpighia emarginata DC.) de boa qualidade. Um fatorial quatro (20:80, 40:60, 60:40 e 80:20% de matéria orgânica:terra) por quatro (húmus de minhoca, casca de arroz carbonizada, pó de casca de coco seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
4
0
3
Order By: Relevance
“…(PENN JUNIOR, 2006; MATHEWS; YUYAMA, 2010). Similar results were reported by Lima et al (2006) who studied alternative substrates containing rice husk ash, powdered dry coconut bark and carnauba palm leaf straw which did not contribute satisfactorily to obtain quality Caribbean cherry seedlings. Mixtures in the substrate to produce araticum were tested and it was reported that the treatments with ash and lime did not differ statistically in height plant or stem diameter.…”
Section: Resultssupporting
confidence: 86%
“…(PENN JUNIOR, 2006; MATHEWS; YUYAMA, 2010). Similar results were reported by Lima et al (2006) who studied alternative substrates containing rice husk ash, powdered dry coconut bark and carnauba palm leaf straw which did not contribute satisfactorily to obtain quality Caribbean cherry seedlings. Mixtures in the substrate to produce araticum were tested and it was reported that the treatments with ash and lime did not differ statistically in height plant or stem diameter.…”
Section: Resultssupporting
confidence: 86%
“…However, more important than the OM content in the substrate for the availability of N to plants is the degree of humification of OM, because the more recalcitrant, the lower its C/N rate, which increases the availability of nitrogen to plants. This information was evidenced by Lima et al (2006) who studied the development of Malpighia emarginata seedlings on substrates with different degrees of humification. Guapeva seedlings grown in the substrate SB+CM showed higher Mg levels (4.1 mg kg -1 ) and S (1.98 mg kg -1 ).…”
Section: Substrate Sdw Ldw Rdw Tdw Sl/rcd R/s Dqi -------------G ----mentioning
confidence: 94%
“…A aceroleira (Malpighia emarginata DC.) é uma planta de crescimento intenso e que apresenta alta demanda por nutrientes, quando cultivada em condições de clima e manejo adequados (LIMA et al, 2006). As plantas iniciam a produção, já a partir do primeiro ano de cultivo, ocasião em que podem produzir até 2 kg de frutos frescos.…”
Section: (Recebido Em 12 De Dezembro De 2006 E Aprovado Em 10 De Seteunclassified
“…Com esse procedimento, é possível manter equilibrada a fertilidade do solo e garantir produtividade e a rentabilidade da cultura. Além disso, o conhecimento dos teores de nutrientes nas folhas é uma medida efetiva para acompanhar a evolução do estado nutricional da cultura e para organizar estratégias eficientes de manejo da adubação mineral visando altas produtividades (LIMA et al, 2006). Villela & Lacerda (1992) mencionaram que a variação sazonal na concentração dos elementos minerais nas folhas está fortemente relacionada aos mecanismos de absorção e de retranslocação.…”
Section: (Recebido Em 12 De Dezembro De 2006 E Aprovado Em 10 De Seteunclassified